Characterisation and evolutionary dynamics of ten novel Gammapapillomavirus types from South African penile swabs - Murahwa, Alltalents Tutsirayi (Department of Pathology, 2019)
Human papillomaviruses (HPVs) are genetically diverse, belonging to five distinct genera: Alpha, Beta, Gamma, Mu and Nu. We discovered ten novel Gammapapillomaviruses (Gamma-HPVs). Genomic characterisation and phylogenetic evaluation of the ten novel Gamma-HPV types were done: HPV211, HPV212, HPV213, HPV214, HPV215, HPV216, HPV219, HPV220, HPV221 and HPV222. These HPVs were previously identified in a study that was done on 218 penile samples (104 HIV negative and 114 HIV positive) using high throughput sequencing (Roche 454) of amplimers obtained using FAP59/64 primers which were designed to detect “cutaneous” or Beta- and Gamma-HPVs. Fifteen putative novel HPV types were identified from the short HPV L1 FAP fragments HPV211 (CT02, KY063000), HPV212 (CT03, KY063001), HPV213 (CT04, KY063002), HPV214 (CT06, KY063004), HPV215 (CT07, KY063005), HPV216 (CT12, KY063010), HPV219 (CT01, KY062999), HPV220 (CT08, KY063006), HPV221 (CT09, KY063007) and HPV222 (CT155, AY009886) with prevalences varying from 0.5% to 4.1% of men sampled. Multiple full genome clones for each novel type were generated through whole genome amplification, cloning and next generation sequencing. Complete genome sizes were: HPV211 (7253 bp), HPV212 (7208 bp), HPV213 (7096 bp), HPV214 (7357 bp), HPV215 (7186 bp), HPV216 (7233 bp), HPV219 (7108 bp), HPV220 (7381 bp), HPV221 (7326 bp) and HPV222 (7275 bp). Phylogenetically the novel Papillomaviruses (PVs) all clustered with Gamma-HPVs: HPV211 is most closely related to HPV168 (72% identity in the L1 nucleotide sequence) of the Gamma-8 species, HPV212 is most closely related to HPV144 (82.9%) of the Gamma-17 species, HPV213 is most closely related to HPV153 (71.8%) of the Gamma-13 species, HPV214 is most closely related to HPV103 (75.3%) of the Gamma-6 species, HPV215 and HPV216 are most closely related to HPV129 (76.8% and 79.2% respectively) of the Gamma-9 species. HPV219 is phylogenetically most closely related to HPV213 (87% identity in L1 gene) of the Gamma-13 species, HPV220 to HPV212 (72%) of Gamma-17, HPV221 to HPV142 (80%) of Gamma-10, HPV222 to HPV162 (73%) of Gamma-19. The novel HPV types demonstrated the classical genomic organisation of Gamma-HPVs, with seven open reading frames (ORFs) encoding five early (E1, E2, E4, E6 and E7) and two late (L1 and L2) proteins. Typical of Gamma-HPVs, the novel types all lacked the E5 ORF and HPV214 also lacked the E6 ORF. We further examined variation of the novel types in clinical specimens from which they were identified. All the clones of HPV211, HPV214, HPV216, HPV219 and HPV221 were identical and showed 100% pairwise identity. The clones of HPV213, HPV215, HPV212, HPV220 and HPV222 had several differences. Analysis of mismatches between the nine genomic clones of HPV212 showed a total of 67 mismatch positions that varied along the 7208 bp genome and all the clones were unique. Analysis of mismatches between the 10 genomic clones of HPV213 showed a total of 51 mismatch positions that varied along the 7096 bp genome and it had 5 unique clones. The 6 genomic clones of HPV215 showed a total of 50 mismatch positions along a 7186 bp genome and it had 3 identical and 3 different clones. HPV220 had 4 different genomic clones that showed 17 mismatch positions along a 7381 bp genome. The 5 different clones of HPV222 showed a total of 24 mismatch positions along the 7275 bp genome. Conserved domains observed among the novel types were the Zinc finger binding Domain and PDZ domains. A retinoblastoma binding protein (pRB) binding domain in the E7 protein was additionally identified in HPV214 and HPV222. PVs are thought to evolve slowly because they co-opt high-fidelity host cellular DNA polymerases for their replication. Despite extensive efforts to catalogue all the HPV species that infect humans, it is likely that many still remain undiscovered. We used the genome sequences of the ten novel viruses and related HPVs to analyse the evolutionary dynamics of these viruses at the whole genome and individual gene scales. We found statistically significant incongruences between the phylogenetic trees of different genes which imply gene-to-gene variation in the evolutionary processes underlying the diversification of Gamma-PVs. We were, however, only able to detect convincing evidence of a single recombination event which, on its own, cannot explain the observed incongruences between gene phylogenies. The divergence times of the last common ancestor (LCA) of the Alpha, Beta, Mu, Nu and Gamma genera was predicted to have existed between 49.7-58.5 million years ago before splitting into the five main lineages. The LCA of the presently sampled Gamma-PVs was predicted to have existed between 45.3 and 67.5 million years ago: approximately at the time when the simian and tarsier lineages of the primates diverged. The discovery, characterisation and classification of HPV211, HPV212, HPV213, HPV214, HPV215 HPV216, HPV219, HPV220, HPV221 and HPV222 add these novel types to the repertoire of the ever expanding Gamma-HPVs genus hence expanding our knowledge of these viruses.